Characteristics of contact force and muscle activation during choreographed falls with 2 common landing techniques in contemporary dance - van Ramshorst, C.; Choi, W. J. (Journal of Applied Biomechanics, 2019)
This study investigated the contact forces and muscle activation during 2 choreographed fall techniques in contemporary dancers and how these were affected by the fall technique. Ten collegiate-level dancers were instructed in 2 choreographed falls: (1) an anteriorly focused fall involving ankle plantar flexion, knee flexion, and hip flexion with dispersion of forces up the anterior surface of the shank (technique 1) and (2) a laterally focused fall involving inversion at the ankle with dispersion of forces up the lateral aspect of the shank (technique 2). The knee and hip contact forces were 26.3% smaller (technique 1: 1743 N vs technique 2: 1284 N) and 24.1% greater (technique 1: 1334 N vs technique 2: 1656 N), respectively, in technique 2 (P<.03). At the time of knee contact, percentage of maximal voluntary isometric contraction (%MVIC) was 45.8% greater for rectus femoris muscle (technique 1: 7.2% vs technique 2: 10.5%) and 96.9% greater for gluteus medius muscle (technique 1: 3.2% vs technique 2: 6.3%) (P<.01) in technique 2. The results provide insight into determining safer landing strategies to avoid knee injuries in individuals who experience a fall (ie, dancers, athletes, and older adults).